Brand Personality Scale: is It Applicable for a Small Emerging Country? - Dikcius, Vytautas; Seimiene, Eleonora; Casas, Ramunas (Organizations and Markets in Emerging Economies, 2018)
In Lithuania, a small emerging country, up to now the J.Aaker brand personality scale has been used without a proper validation. Previous researchers have made conclusions that the J.Aaker brand personality scale is both culture- and country-sensitive. Moreover, some studies show that not all dimensions might be suitable for measuring brand personality in a specific country or cross-cultural studies. Therefore, this paper aims to adapt and validate the scale proposed by J. Aaker in a context of a small emerging country. The scale validation takes place in several stages: starting with a qualitative study, involving experts, and finishing with an extensive quantitative study in three product categories. The research has revealed that in the Lithuanian context, the brand personality scale is composed of three dimensions, such as Sincerity, Modernity-Excitement and Competence. The scale, valid for a small emerging country, consists of 13 instead of 42 traits.
Keywords: brand personality; brand personality scale; emerging economy; scale validation